Simpanan Biji Gulma dalam Tanah di Perkebunan Teh pada Berbagai Tahun Pangkas - Edi Santosa; Sofyan Zaman; Intan Dewi Puspitasari (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Through understanding on seed bank, tea plantation manager enables to plan better weed control. The objective of the study was to identify seed bank of weeds at different ages of tea plantation after prunning. The study was conducted at Perkebunan Teh Tambaksari, Subang, Indonesia. Soil samples were collected from tea field of different pruning years (TP0-2 months after pruning, TP1-16 months after pruning, TP2- 28 months after pruning, and TP3-40 months after pruning) and then watered regularly and exposed to direct sunshine to stimulate propagule germination. Results showed that seed banks were found in all soil samples, indicated that effectiveness of weed control was low. The highest seed bank was found at TP1. Most seed bank was seed, they were Ageratum conyzoides which dominated field of TP0 (SDR 36.58%), TP1 (35.90%), TP2 (41.79%) and TP3 (24.82%), followed by Borreria latifolia with SDR values were 19.50%, 27.26%, 29.40% and 16.14%, respectively. Some species stored both vegetative and generative propagules such as Cyperus sp. and Cyperus cyperoides with SDR value 20.33 % only dominated at age of TP0. Seed bank at area of TP1 and TP2 had high value of community coefficient, i.e., 77.22%, showed both fields had high similarity. This finding implies that effective weed control increases when the control is conducted before the weeds bear seed, where mostly less than 45 days after emergence. Furthermore, thirteen weeds had no seed bank in the field, indicates that weed problem in tea plantation was composed of seed bank and weed propagules from other sites.   Key words:  Pruning year, seed bank, tea plantation, weed control